Faktor - Faktor yang Berhubungan dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan di wilayah kerja UPT Puskesmas Pemulutan Kabupaten Ogan Ilir Tahun 2025 - Amrina; Erma Puspita Sari; Merisa Riski; Sendy Pratiwi Ramadhani (STIKes Budi Mulia Sriwijaya, 2025)
Stunting is a condition in which toddlers experience chronic nutritional deficiencies over a long period, resulting in growth disorders characterized by height shorter than the standard for their age.This study aimed to determine the factors associated with stunting among children aged 24–59 months in Ogan Ilir Regency in 2025. Method his was a quantitative study with an observational analytic approach using a case-control design. The research was conducted at UPT Puskesmas Pemulutan with samples of children aged 24–59 months selected through purposive sampling. Data were collected using questionnaires and observations, and analyzed using the Chi-Square test. Results The findings showed significant associations between nutritional status (p=0.000), maternal knowledge (p=0.000), and environmental sanitation (p=0.000) with stunting among children aged 24–59 months at UPT Puskesmas Pemulutan, Ogan Ilir Regency in 2025. Conclusion Nutritional status, maternal knowledge, and environmental sanitation are significantly associated with stunting among children aged 24–59 months in the working area of UPT Puskesmas Pemulutan in 2025.